Do Green Bonds Matter? Evidence From Stock Market Responses In ASEAN Developing Countries - Nurhaflah Soraya; Khairi Anshor (Worksheet : Jurnal Akuntansi, 2026)
This study investigates the stock market reaction to the announcement of green bond issuances by companies operating in developing ASEAN countries. Using an event study methodology, the findings reveal no statistically significant abnormal returns before and after the announcement dates. This suggests that capital markets in the region have yet to respond to sustainable finance instruments such as green bonds meaningfully. The weak market reaction may reflect limited integration of sustainability considerations into pricing mechanisms, low investor awareness, and insufficient trust in corporate environmental commitments. The study underscores the need for issuers to enhance disclosure quality, particularly concerning project transparency, measurable environmental impact, and fund utilization governance. Market regulators and financial institutions should also strengthen the regional sustainable finance ecosystem through regulatory support, fiscal incentives, and investor education. Future research is recommended to expand the dataset across ASEAN countries and incorporate ESG ratings, bond certification types, and environmental policy stability to better understand market dynamics.